2022
DOI: 10.2147/ijgm.s360160
|View full text |Cite
|
Sign up to set email alerts
|

Different Aspects of Diabetes in Hospitalized Patients with COVID-19

Abstract: Background The novel severe acute respiratory syndrome coronavirus (SARS-CoV-2) causes COVID-19, a recent infectious disease that aggravates the underlying pathophysiology of hyperglycemia in diabetic individuals. This study aimed to detect how diabetes mellitus (DM) affected COVID-19 patients’ morbidity and mortality, and the incidence of neonset DM. Patients and Methods The present study was a cross-sectional study done at Aswan Isolation Hospitals, Egypt. It comprise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Inflammatory markers such as ESR, CRP, and ferritin are significantly correlated with COVID-19 severity and outcomes. [22][23][24] CRP is a partial mediator of the correlation between the severity of COVID-19 and DM, confirming the importance of inflammation in the pathogenesis of COVID-19 severity in diabetic patients. 25 Similar to our findings, Guo et al 26 found that diabetic patients had a higher level of CRP (44.8 mg/L vs. 25.8 mg/L; p = 0.003) compared with non-diabetic patients with COVID-19.…”
Section: Discussionmentioning
confidence: 63%
“…Inflammatory markers such as ESR, CRP, and ferritin are significantly correlated with COVID-19 severity and outcomes. [22][23][24] CRP is a partial mediator of the correlation between the severity of COVID-19 and DM, confirming the importance of inflammation in the pathogenesis of COVID-19 severity in diabetic patients. 25 Similar to our findings, Guo et al 26 found that diabetic patients had a higher level of CRP (44.8 mg/L vs. 25.8 mg/L; p = 0.003) compared with non-diabetic patients with COVID-19.…”
Section: Discussionmentioning
confidence: 63%
“…The coronavirus disease 2019 (COVID-19) is a life-threatening condition caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection. Since the beginning of the pandemic, diabetes mellitus (DM) emerged as a major comorbidity for COVID-19 severity and mortality [1][2][3][4][5][6][7]. Fortunately, the advent of SARS-CoV-2 vaccines reduced the incidence of COVID-19 post-acute sequelae and comorbidities [8,9].…”
Section: Introductionmentioning
confidence: 99%